2007
DOI: 10.1111/j.1464-410x.2007.06657.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin‐D receptor (Fok‐I) gene polymorphism with bladder cancer in an Indian population

Abstract: RESULTSThere was a significant difference in genotype and allelic distribution of VDR (Fok-I) polymorphism in the patients ( P = 0.033 and = 0.017, respectively). The FF genotype was associated with twice the risk for bladder cancer (odds ratio 2.042, 95% confidence interval, CI,). There was no significant difference in genotypic distribution or allelic frequencies of the VDR (Taq-I) polymorphism ( P = 0.477 and 0.230) when compared with the controls. The stage and grade of the bladder tumours had no associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 31 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…Moreover, these differences might also result from confounding factors that are taken into consideration in these studies and include food habits, age, education, menopausal status, parity, body-mass index, use of oral contraceptives or hormone replacement therapy, tubal ligation, and others (Lurie et al, 2007(Lurie et al, , 2011Tworoger et al, 2009). The BsmI or FokI SNPs in VDR have been associated with breast, bladder, renal, carcinoma, and cutaneous malignant melanoma and nonmelanoma skin cancer (Mittal et al, 2007;Gandini et al, 2009;Tang et al, 2009;Arjumand et al, 2012). These polymorphisms were also recognized as risk factors of hepatocellular, head and neck, thyroid, prostate, and colorectal cancers (Liu et al, 2005;Mishra et al, 2005;Bai et al, 2009Bai et al, , 2012Penna-Martinez et al, 2009;Falleti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these differences might also result from confounding factors that are taken into consideration in these studies and include food habits, age, education, menopausal status, parity, body-mass index, use of oral contraceptives or hormone replacement therapy, tubal ligation, and others (Lurie et al, 2007(Lurie et al, , 2011Tworoger et al, 2009). The BsmI or FokI SNPs in VDR have been associated with breast, bladder, renal, carcinoma, and cutaneous malignant melanoma and nonmelanoma skin cancer (Mittal et al, 2007;Gandini et al, 2009;Tang et al, 2009;Arjumand et al, 2012). These polymorphisms were also recognized as risk factors of hepatocellular, head and neck, thyroid, prostate, and colorectal cancers (Liu et al, 2005;Mishra et al, 2005;Bai et al, 2009Bai et al, , 2012Penna-Martinez et al, 2009;Falleti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported dietary intake of vitamin D is a less accurate measure vitamin D status than are serum or tissue 25(OH)D concentrations, however. One study reported bladder cancer risk to be higher among persons with alleles of the vitamin D receptor rs10735810 polymorphism (“ Fok1” ) that are known to decrease the receptor’s activity (16). …”
Section: Introductionmentioning
confidence: 99%
“…One study (Liu et al, 2005) showed a significant 36% inverse association for head and neck cancer. Two more studies observed a significant inverse association with bladder (Mittal, Manchanda, Bhat, & Bid, 2007) and brain cancer risks (Anic et al, 2012) comparing Ff with FF genotype.…”
Section: Other Cancer Sitesmentioning
confidence: 96%